Competing contestations of the norm: emerging sexualities and digital identities. Issue 5 (3rd September 2019) - Cover, Rob
ABSTRACT: This article investigates competing ways in which challenges to normativity are produced in young people's discourse on sexual identity in online settings particularly in terms of the production of 'contested belonging.' It is interested in how some competing discourses that emerge are taken up through having or being given 'voice' while other alternative frameworks of identity are not. The article is interested in juxtaposing emerging challenges to the hetero/homo binary, and the narrow performativities of belonging and inclusion invoked in neoliberal inclusions of the latter term (as LGBTI tolerance, marriage equality, etc.). The article examines the challenge arising from a more populist, everyday youth creative expression online in the development of new identity labels, categories and articulations of belonging (such as ace/asexual identity, sapiosexuality, heteroflexibility) that sit outside the norms of the hetero/homo binary. Emerging in co-creative, digital and interactive settings, this 'challenge from below' likewise critiques norms, but from a perspective focused on inclusivity while retaining subjectivity and self-authenticity at its core. The paper assesses this challenge to normativity to answer the question: what has voice to contest, and in what are the conditions necessary for the sound of the voice of contesting discourse to be recognized and heard .